2007
DOI: 10.1016/j.phytochem.2007.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Transport of camptothecin in hairy roots of Ophiorrhiza pumila

Abstract: We have investigated the subcellular accumulation and transport of camptothecin (CPT), a monoterpene indole alkaloid, in hairy roots of Ophiorrhiza pumila. This hairy root produces high amounts of CPT and excretes it into the culture medium. When the hairy roots were exposed to UV radiation, autofluorescence emitted from CPT showed subcellular localization of CPT in the vacuole. Treatment with several inhibitors suggested that CPT excretion is a transporter-independent passive transport controlled by the conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Camptothecin has been reported to be accumulated in the glandular trichomes of leaves and stems of C. acuminata (Li et al 2002). Subcellular localization studies showed that camptothecin is accumulated in the vacuole, which is considered to be a site for avoiding toxicity (Pasqua et al 2004;Sirikantaramas et al 2007c). Interestingly, in the hairy roots of O. pumila (Saito et al 2001), camptothecin is partially accumulated in the vacuole and partially excreted to the culture medium (Sirikantaramas et al 2007c).…”
Section: Alkaloid Detoxification Mechanisms By Sequestrationmentioning
confidence: 99%
“…Camptothecin has been reported to be accumulated in the glandular trichomes of leaves and stems of C. acuminata (Li et al 2002). Subcellular localization studies showed that camptothecin is accumulated in the vacuole, which is considered to be a site for avoiding toxicity (Pasqua et al 2004;Sirikantaramas et al 2007c). Interestingly, in the hairy roots of O. pumila (Saito et al 2001), camptothecin is partially accumulated in the vacuole and partially excreted to the culture medium (Sirikantaramas et al 2007c).…”
Section: Alkaloid Detoxification Mechanisms By Sequestrationmentioning
confidence: 99%
“…Based on the pattern described for ceramides (Shin et al 2014) and camptothecin (Zhao 2010 The chemical identification of the ligand of Pru p 3 was also confirmed by its capacity to emit blue light when excited with UV radiation (254 nm; Fig. 3a), a feature also shown by camptothecin (Sirikantaramas et al 2007). Moreover, camptothecin is well known for its ability to inhibit the catalytic activity of topoisomerase I, the enzyme responsible for relaxing supercoiling DNA (Wright et al 2015).…”
Section: The Ligand Of Pru P 3 Included a Hydroxylated Derivative Of mentioning
confidence: 80%
“…In many cases, secondary metabolites and their pathway intermediates are phytotoxic. Plants have evolved several defence mechanisms to avoid self-toxicity from secondary metabolites (Sirikantaramas et al 2007). A basic strategy to avoid self-toxicity is tight regulation of biosynthesis in terms of temporal/spatial gene expression and localization.…”
Section: Discussionmentioning
confidence: 99%
“…Since it possesses topoisomerase I poisoning properties, its semi-synthetic derivatives, topotecan and irinotecan, have been developed to be clinically used as anticancer drugs. Previously, we have established a hairy root culture of O. pumila which has already been shown to be a desirable experimental system to study the biosynthesis of camptothecin, since the culture produces a high level of CPT and excretes it into the culture medium (Sirikantaramas et al 2007 ).…”
Section: Camptothecin (Cpt)mentioning
confidence: 99%